Sludge treatment and disposal - Andreoli, Cleverson Vitorio; Sperling, Marcos von; Fernandes, Fernando (Biological wastewater treatment series ;, 2007)
Sludge Treatment and Disposal is the sixth volume in the series Biological Wastewater Treatment. The book covers in a clear and informative way the sludge characteristics, production, treatment (thickening, dewatering, stabilisation, pathogens removal) and disposal (land application for agricultural purposes, sanitary landfills, landfarming and other methods). Environmental and public health issues are also fully described. About the series: The series is based on a highly acclaimed set of best selling textbooks.